Growth and Yield of Wheat (Triticum aestivum) under Varying Levels of Irrigation and Fertilizer in Eucalyptus Based Agrisilviculture System - Deswal, A.K.; Nandal, D.P.S. (Indian Journal of Agroforestry, 2020)
A field experiment was conducted on sandy loam soil during the winter seasons of 2003-04 and 2004-05 at research farm of CCS Haryana Agricultural University, Hisar, to study the effect of different irrigation levels viz., no post sowing irrigation, two irrigations at 22 and 85 days after sowing (DAS), four irrigations at 22, 45, 85 and 105 DAS, and six irrigations at 22, 45, 65, 85, 105 and 120 DAS, and four fertilizer levels (0, 75, 100 and 125 per cent of the recommended dose of 150 kg N and 60 kg P2O5 ha-1) on growth and yield attributes of wheat (Triticum aestivum L.) intercropped with 4-5 years old plantation of Eucalyptus tereticornis (6 m x 2 m) vis-a-vis sole wheat. In Eucalyptus based agrisilviculture system, application of six irrigations and 125 per cent of recommended dose of fertilizer resulted in higher value of growth and yield attributing parameters and consequently higher grain yield of wheat. In sole wheat, maximum value of growth and yield parameters and consequently yield was recorded at two irrigations and 100 per cent of the recommended fertilizer dose. However, irrigation treatments had no significant effect on grain yield of sole wheat.